Perancangan Pemancar Dan Penerima Modulasi Digital FSK Berbasis Serat Optik Menggunakan Metode Splising Dan Adapter Untuk Modul Praktikum Optik - aprinal adila asril (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2019)
This research aims to design practicum modules for optical cable transmission systems with fiber optic cable (fiber optic) connection systems. This research was conducted by design and experimental methods. The practicum module that is designed consists of the transmitter and receiver parts using a Digital modulation system. The results of this module design will be tested, measured, and analyzed in the delivery of information using FSK digital modulation and the damping effect of informatio received due to the connection of optical fibers to the transmission system. Splicing is done using the fusion splicer (splising) method and adapters. The two connection methods will be compared to the measurement results, especially the damping value. The results of the study are an Optical practicum module using optical signal transmission media as well as a practicum module (jobsheet). The module that is designed will be one of the Practicum modules to support the eyes of the optical fiber communication system in the State Polytechnic Telecommunications Engineering Study Program.